From national monument to national park: changes in community capitals - Ricketts, Taylor (Kansas State University, 2015)
National monument to national park re-designation can be identified as a controversial issue that poses an array of implications for surrounding communities. These perceived implications have the ability to create or change policies, regulations, economic development, marketing, quality of life and other direct or indirect impacts to communities. In 2010, Grand Junction, Colorado proposed re-designation of the Colorado National Monument to a national park. The community expressed split views on the issue expressing concerns on issues such as the preservation, traffic, regulated uses, restrictions, government imposition, property values, infrastructure, costs, economic prosperity and other impacts that might occur from re-designation. A multiple case study was conducted in order to determine if there were any significant impacts to other communities that had gone through similar re-designation efforts. The Community Capital Framework was used in determining the assets investigated for the years of 2000 and 2010. The findings of this study suggest that there are no substantial apparent impacts within the locations of past re-designation. Grand Junction had somewhat parallel findings to the other sites, even without the presence of re-designation. Suggesting, the re-designation efforts should be focused less on the community impacts and more on the short-term vs long-term park/monument effects.
Keywords: Community Capital Framework; National monument; National park; Re-designation; Community controversy; Recreation and Tourism (0814); Urban Planning (0999)